Characterization and comparison of injuries caused by accidental and non-accidental blunt force trauma in dogs and cats - Intarapanich, Nida P; Mccobb, Emily; Reisman, Robert W; Rozanski, Elizabeth A; Intarapanich, Pichai P (Journal of Forensic Sciences, 2016)
Motor vehicle accidents (MVA) are often difficult to distinguish from non-accidental injury (NAI). This retrospective case–control study compared animals with known MVA trauma against those with known NAI. Medical records of 426 dogs and cats treated after MVA and 50 after NAI were evaluated. Injuries significantly associated with MVA were pelvic fractures, pneumothorax, pulmonary contusion, abrasions, and degloving wounds. Injuries associated with NAI were fractures of the skull, teeth, vertebrae, and ribs, scleral hemorrhage, damage to claws, and evidence of older fractures. Odds ratios are reported for these injuries. MVA rib fractures were found to occur in clusters on one side of the body, with cranial ribs more likely to fracture, while NAI rib fractures were found to occur bilaterally with no cranial–caudal pattern. Establishing evidence-based patterns of injury may help clinicians differentiate causes of trauma and may aid in the documentation and prosecution of animal abuse. © 2016 American Academy of Forensic Sciences
33 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-209-501-358-961 tex.type: [object Object]
Keywords: animal; blunt force trauma; dept.mat; dog; forensic science; injury; motor vehicle accident; non-accidental injury; veterinary